COACHING FAMILY-BASED OUTPATIENT TREATMENT METHOD FOR ADOLESCENT ANOREXIA NERVOSA. A CASE REPORT. - JAANA RONKAINEN, JUKKA RONKAINEN (Psychiatria Fennica)
ABSTRACT Family-based treatment (FBT) has been shown to be an effective treatment for adolescent anorexia nervosa and the method is nowadays generally recommended, but probably not widely enough in practice in Finland. Around a decade ago, one severe anorexia patient was successfully treated by a paediatrician (JR), in an initially unplanned treatment, at a healthcare centre as an outpatient, by coaching the family to return the patient to their previous normal eating habits. The severe malnutrition (weight loss of 20 kgs and body mass index 14.3 kg/m2) and the eating disorder symptoms alleviated in approximately six months by actively supporting and coaching the parents, in weekly appointments, to take whole responsibility for the meals. During the last ten years, the paediatrician (JR) has applied the coaching family-based method (c-FBM) to all adolescent patients with a restrictive eating disorder seeking help, first at the Primary Healthcare Centre of Oulu, and lately at Primary Healthcare Centres of Länsi-Pohja District and at a private clinic in Oulu. The c-FBM is otherwise quite similar to the generally used FBT method, with the most significant difference being the primary care paediatrician taking the main responsibility for the treatment. In this article we introduce the c-FBM through four lately treated patient cases who have all benefited from the treatment within one year.